Implications biopsychosocial of pregnancy in adolescence (Research, Society and Development, 2025)
Introduction: Teenage pregnancy is considered a public health challenge in developing countries, with serious health implications, including maternal and neonatal mortality. Objective: To analyze in detail the biopsychosocial implications of teenage pregnancy. Methodology: This is an integrative review, carried out in the databases National Library of Medicine (PubMed/MEDLINE), Cochrane Library, Science Direct, Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and PERIÓDICO CAPES, between the years 2019 and 2023. Results: It was found that the 09 articles selected and characterized in the final sample were from international productions (100%), three coming from Africa (33.3%), two from the United States of America. America (22.2%), two from Canada (22.2%), one from Spain (11.1%) and one from Ireland (11.1%). Regarding the languages found in the literature, there were eight in English (88.9%) and one article in Spanish (11.1%). The biopsychosocial implications of teenage pregnancy were identified, seven addressing mental disorders, five economic vulnerability, three articles talk about school dropout, seeking abortion, single parenthood and marginalization, two studies mention substance abuse, social stigmas, maternal and child mortality, low self-esteem and social isolation and one article presents low Apgar scores, sexual violence, emotional abuse, eating disorders, poor health care, affected psychosocial support and persecution from family members. Conclusion: The study identified the importance of examining the biopsychosocial implications during the teenage pregnancy process.